Probing mutation-induced conformational transformation of the GTP/M-RAS complex through Gaussian accelerated molecular dynamics simulations - Huayin Bao; Wei Wang; Haibo Sun; Jianzhong Chen (Taylor & Francis Group, 2023)
Mutations highly affect the structural flexibility of two switch domains in M-RAS considered an important target of anticancer drug design. Gaussian accelerated molecular dynamics (GaMD) simulations were applied to probe the effect of mutations P40D, D41E, and P40D/D41E/L51R on the conformational transition of the switch domains from the GTP-bound M-RAS. The analyses of free energy landscapes (FELs) not only reveal that three mutations induce less energetic states than the wild-type (WT) M-RAS but also verify that the switch domains are extremely disordered. Principal component analysis (PCA) and dynamics analysis suggest that three mutations greatly affect collective motions and structural flexibility of the switch domains that mostly overlap with binding regions of M-RAS to its effectors, which in turn disturbs the activity of M-RAS. The analyses of the interaction network between GTP and M-RAS show that the high instability in hydrogen bonding interactions (HBIs) of GTP with residue 41 and Y42 in the switch domain I drives the disordered states of the switch domains. This work is expected to provide a molecular mechanism for deeply understanding the function of M-RAS and future drug design towards the treatment of cancers.